2015
DOI: 10.1021/acsami.5b03537
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheet-Assembled ZnFe2O4 Hollow Microspheres for High-Sensitive Acetone Sensor

Abstract: Semiconductor oxides with hierarchically hollow architecture can provide significant advantages as sensing materials for gas sensors by facilitating the diffusion of target gases. Herein, we develop a facile template-free solvothermal strategy combined with the subsequent thermal treatment process toward the successful synthesis of novel ZnFe2O4 hollow flower-like microspheres. The images of electron microscopy unambiguously indicated that the ZnFe2O4 nanosheets with thickness of around 20 nm assembled hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(82 citation statements)
references
References 57 publications
(65 reference statements)
2
80
0
Order By: Relevance
“…Based on the above comparative experimental results, we speculated that the possible growth pattern and formation mechanism of such hierarchical hollow Bi 2 WO 6 microspheres assembled by thin nanoplates could be attributed to the typical Ostwald ripening mechanism, which has been employed as a template-free strategy to get inorganic hollow structures via an "inside-out" mechanism that thermo-dynamically less stable matter in the core of solid aggregates is dissolved and scattered into the surface, the hollow structures were obtained by continuous evacuation of the core materials [23,24]. Many hollow nano/micro structures have been reported according to this classic Ostwald ripening formation mechanism, such as hierarchical flower-like Bi 2 MoO 6 hollow spheres [25], CeO 2 hollow nanospheres [26], nanosheet-assembled ZnFeO 4 hollow microspheres [27], double-wall Cu 2 O hollow spheres [28]. Scheme 1 illustrates the possible representation for shaped process of as-obtained hierarchical hollow Bi 2 WO 6 microspheres (Steps 1-3).…”
Section: Formation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above comparative experimental results, we speculated that the possible growth pattern and formation mechanism of such hierarchical hollow Bi 2 WO 6 microspheres assembled by thin nanoplates could be attributed to the typical Ostwald ripening mechanism, which has been employed as a template-free strategy to get inorganic hollow structures via an "inside-out" mechanism that thermo-dynamically less stable matter in the core of solid aggregates is dissolved and scattered into the surface, the hollow structures were obtained by continuous evacuation of the core materials [23,24]. Many hollow nano/micro structures have been reported according to this classic Ostwald ripening formation mechanism, such as hierarchical flower-like Bi 2 MoO 6 hollow spheres [25], CeO 2 hollow nanospheres [26], nanosheet-assembled ZnFeO 4 hollow microspheres [27], double-wall Cu 2 O hollow spheres [28]. Scheme 1 illustrates the possible representation for shaped process of as-obtained hierarchical hollow Bi 2 WO 6 microspheres (Steps 1-3).…”
Section: Formation Mechanismmentioning
confidence: 99%
“…Many hollow nano/micro structures have been reported according to this classic Ostwald ripening formation mechanism, such as hierarchical flower-like Bi2MoO6 hollow spheres [25], CeO2 hollow nanospheres [26], nanosheet-assembled ZnFeO4 hollow microspheres [27], double-wall Cu2O hollow spheres [28]. Scheme 1 illustrates the possible representation for shaped process of as-obtained hierarchical hollow Bi2WO6 microspheres (Steps 1-3).…”
Section: Formation Mechanismmentioning
confidence: 99%
“…The work principle for the type of gas sensors is that the resistance change of the sensors is resulting from the interaction between the tested gas molecules and active sites on the surface of sensing material [4][5][6][7]. It is well-known that the chemical component and the microstructure play key roles in the gas-sensing characteristics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The transient current of ZnFe 2 O 4 reflects a faster oxidation of 2propanol than 1-propanol on the surface. [16][17] It is observed that under fixed operational conditions, transient currents in the [a] Dr. The calculations predict more spontaneous adsorption of 2-propanol on the (111) surface of ZnFe 2 O 4 than 1-propanol.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Several metal-oxides that are used as a catalyst for the aerobic oxidation of organic molecules are semiconductors (e. g. TiO 2 , ZnO, Fe 2 O 3 ) and also act as chemiresistors for the detection of vapor phase organic analytes. [16][17] It is observed that under fixed operational conditions, transient currents in the [a] Dr. [11][12][13][14] Investigating the operation principle of SMO chemiresistors, it is identified that their transient current in response cycle is basically the reflection of collective interactions (e. g., adsorption, diffusion, and aerobic oxidation) of target analyte on the respective metal-oxide surface.…”
mentioning
confidence: 99%